Listeriosis in pregnancy: a common yet underdiagnosed cause of febrile illness. - Rubab Riaz; Rubina Shaheen (Journal of University Medical & Dental College, 2022)
Food borne listeria infection is common in pregnancy compared to the general population because of the reduced immune defense mechanism in pregnancy. It may cause maternal morbidity and fetal mortality if not treated on time. Precooked meat and milk products are the main source of listeria. The diagnosis is confirmed by blood culture, and the infection is cured with ampicillin. This case report is of a patient presenting with febrile illness in the second trimester of pregnancy. She gets promptly investigated for possible differential diagnosis, bacterial, viral, and protozoal. Maternal complication increased till definitive management is offered.